Effectiveness Of Coaching And Mentoring For Employee Career Development Within The Organization - Syailendra, Siera; Setiawan, Mulkan; Sopian; Kusuma Atmaja, Efri Kusuma Atmaja; Rati Sari (Jurnal Ecoment Global, 2023)
Objective: This study aims to determine the effectiveness of coaching and mentoring for the career development of employees in organizations. Design/Methods/Approach: This study uses the research method used is the observation method, the library method, internet review and the analysis process is carried out using the literature review analysis method of previous journals.   Findings: Employees must know specifically what to do and be able to face obstacles to achieve effective performance, this is where coaching, mentoring and career counseling activities are needed. Originality/Value: Coaching and Mentoring are important for improving employee performance and providing different benefits for the organization. Practical/Policy implication: The results of the study show that coaching and mentoring help improve employee performance and setting goals leads to higher performance through increasing effort and motivation levels of employees, one of which is through career counseling.